Manajemen Privasi di Situs Jejaring Sosial: Studi Kasus Penggunaan Finstagram untuk Voyeurisme Termediasi - Alya Nurbaiti; Irham Nur Anshari (Jurnal Media dan Komunikasi Indonesia, 2020)
In 2015, Instagram users started to create secondary accounts dubbed finstagram (fake Instagram) to fulfill the unmet needs of using the main account. Among the needs is to do mediated voyeurism or stalking — the act of watching other’s lives through the means of the media — safely. Prior Instagram studies have been more focused on the self-disclosure discourse while analysis on the voyeurs as consumers of disclosure is lacking. Using the case study method, this paper records the exercise of mediated voyeurism through finstagram and the privacy management that occurs within. The result shows that the use of finstagram for mediated voyeurism is driven by the perceived privacy risk (perceived risk of possible privacy violations). The perceived privacy risk encourages voyeur to navigate privacy management by adopting protecting behavior, or various forms of action taken to protect the exercise of stalking.